2007
DOI: 10.1021/ol063072p
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Chiral Quaternary Carbon Stereocenters Using Silylene Transfer Reactions:  Enantioselective Synthesis of (+)-5-epi-Acetomycin

Abstract: Chiral quaternary carbon stereocenters can be established with high diastereoselectivity by a silylene transfer/Ireland-Claisen rearrangement. The utility of this method was demonstrated by application to a synthesis of (+)-5-epi-acetomycin. [reaction: see text]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…In the reported example to synthesize silalactones, Shindo and coworkers synthesized similar five-membered silalactones by the oxidative cleavage of the siliconÀcarbon bond by treatment with iodine or N-iodosuccinimide (NIS) and demonstrated that addition of a Grignard reagent to silalactones occurs at the silicon center to give trialkylsilyl carboxylic acid (Scheme 2). [5,6] Based on this inspiring report, we initially anticipated that disilalactones (R)-3 might be formed by oxidative dehydrogenation. However, it turned out that no oxidative treatment was actually required, as hydrogen gas evolved spontaneously from this intermediate to give disilalactones.…”
Section: Dedicated To Professor Eun Lee On the Occasion Of His Retirementioning
confidence: 99%
“…In the reported example to synthesize silalactones, Shindo and coworkers synthesized similar five-membered silalactones by the oxidative cleavage of the siliconÀcarbon bond by treatment with iodine or N-iodosuccinimide (NIS) and demonstrated that addition of a Grignard reagent to silalactones occurs at the silicon center to give trialkylsilyl carboxylic acid (Scheme 2). [5,6] Based on this inspiring report, we initially anticipated that disilalactones (R)-3 might be formed by oxidative dehydrogenation. However, it turned out that no oxidative treatment was actually required, as hydrogen gas evolved spontaneously from this intermediate to give disilalactones.…”
Section: Dedicated To Professor Eun Lee On the Occasion Of His Retirementioning
confidence: 99%
“…109,113,114 By forming a silver silylenoid reactive intermediate, Woerpel and coworkers enabled involvement of divalent silylenes in pericyclic reactions involving silacarbonyl ylides 115 to afford synthetically useful products. 82,116,117 While exploring the scope of silver-catalyzed silylene transfer to olefins, Woerpel and Calad observed that the electrophilic silver silylenoid species reacted preferentially with the enolizable ester group to produce vinylsilane 129 instead of a an allyl substituent (e.g., 130h) to reaction conditions facilitated an Ireland-Claisen rearrangement after the initial electrocyclization. This process was highly diastereoselective; the reaction of ester 130h produced silalactone 135 with three contiguous stereocenters as a single isomer.…”
Section: Silver-mediated Transfer Of Di-tert-butylsilylene To Carbonymentioning
confidence: 99%
“…Diol 137 was generated from silalactone after reduction of the lactone moiety with lithium aluminum hydride followed by oxidation of the C--Si bond. 65 116 The reaction of ester 130j revealed that the facial selectivity of the 6p-electrocyclization could not be controlled. Exposure of (Z)-allyl ester 130k to reaction conditions produced a mixture of silalactones 142 and 143.…”
Section: T-bu T-bumentioning
confidence: 99%
See 2 more Smart Citations